82.9k views
3 votes
Help me please, i need it fast

Help me please, i need it fast-example-1
Help me please, i need it fast-example-1
Help me please, i need it fast-example-2

1 Answer

5 votes

Answer:

2) C. (x - 3)² + (y + 2)² = 25

5) x² + y² - 8x - 16y + 54 = 0

6) x² + y² - 10x - 12y + 36 = 0

Step-by-step explanation:

2)

center of circle = 3, -2

x1, y1

end point of circle = 7, 1

x2, y2

the equation of a circle is Pythagorean theorem

x² + y² = r² (where r is the radius of a circle)

distance between points

(x2 - x1)² + (y2 - y1)² = r²

(7 - 3)² + (1 - (-2))² = r²

r² = 25

therefore the equation to the circle is

(x - 3)² + (y + 2)² = 25

=========================================

5)

write the general form of a circle with the center (4,8)

and containing the point (-1, 7)

distance between points

(x2 - x1)² + (y2 - y1)² = r²

(-1 - 4)² + (7 - 8)² = r²

r² = 26

(x - 4)² + (y - 8)² = 26

(x - 4)(x - 4) + (y - 8)(y - 8) = 26

x² - 8x + 16 + y² - 16y + 64 -26 = 0

x² + y² - 8x - 16y + 54 = 0

=========================================

6)

find the general form of a circle with center (5,6)

and tangent to the y-axis.

center (5,6)

h, k

radius = r²

r = 5

(x - h)² + (y - k)² = r²

(x - r)² + (y - k)² = r²

(x - 5)(x - 5) + (y - 6)(y - 6) = r²

x² - 10x + 25 + y² - 12y + 36 = 25

x² + y² - 10x - 12y + 36 = 0

=========================================

User Swizec Teller
by
6.4k points